Accountability of Criminal Actors Terrorism Funding - Bastianto Nugroho; M. Roesli; Surti Yustianti (YURISDIKSI : Jurnal Wacana Hukum dan Sains, 2018)
The word terrorist and terrorism comes from the Latin word terrere which means more or less shaking or vibrating. The word terror can also cause horror. Of course, the horror of the victim's heart and mind. Furthermore, the term terrorism is a concept that has a sensitive connotation because terrorism causes the killing and misery of innocent people. However, until now there is no definition that can be universally accepted. Understanding terrorism for the first time discussed in the European Convention on the Suppression of Terrorism (ECST) in Europe in 1977 there was an expansion of the meaning paradigm from Crimes Against State to Crimes Against Humanity. Crimes Againts Humanity includes criminal acts to create a situation that results in individuals, groups and the general public in an atmosphere of terror. The association of terrorism with the issue of human rights violations, because of the consequences of terrorism, many of the interests of mankind are sacrificed, innocent people are made the cost of savagery and peace of life between human beings is clearly at stake. In this case there is a religious social community that introduces forms of religious implementation as a struggle strategy. The writing of this article is normative by tracing and systematically reviewing the laws and regulations associated with the criminal responsibility of financing terrorism, as well as the opinions of experts from various literature both books, articles and other freelance related to criminal law.